2017
DOI: 10.5530/pj.2017.2.46
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Alpha-Glucosidase and Antioxidant Test of Stem Bark Extracts of Garcinia fruticosa Lauterb

Abstract: Introduction: Diabetes mellitus (DM) is one of the global health emergencies that characterized by high blood glucose levels (hyperglycemia). Type 2 DM is the most common type in diabetic populations. Inhibition of alphaglucosidase can ameliorate postprandial hyperglycemia that occurs in patients with type 2 DM. Adding antioxidants to the therapy of DM is intended to reduce complications caused by oxidative stress. Some species of Garcinia have been proven to inhibit alpha-glucosidase and have antioxidant acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 7 publications
1
15
0
1
Order By: Relevance
“…patens manifest better α -glucosidase inhibitory effect with IC 50 = 26.07 μ g/ml and 30.18 μ g/ml, respectively, than dichloromethane-ethyl acetate and methanol-water extracts which did not exhibit activity. Their results coincide with those reported by other authors, who have demonstrated that high polarity extracts are more active than acarbose [ 35 – 37 ].…”
Section: Resultssupporting
confidence: 92%
“…patens manifest better α -glucosidase inhibitory effect with IC 50 = 26.07 μ g/ml and 30.18 μ g/ml, respectively, than dichloromethane-ethyl acetate and methanol-water extracts which did not exhibit activity. Their results coincide with those reported by other authors, who have demonstrated that high polarity extracts are more active than acarbose [ 35 – 37 ].…”
Section: Resultssupporting
confidence: 92%
“…Test was conducted in a 96-well plate according to Zahratunnisa et al 21 with slight modification. 20 µL stock solution of extracts in different concentrations (100, 500, 1000, 1500, 2000 ppm) and 180 µL of DPPH solution 0.147 mM were added to each well.…”
Section: Introductionmentioning
confidence: 99%
“…Two fractions with the higher percent inhibition compared to other factions are fraction 8 from ethyl acetate extract (FEA8) and fraction 3 from methanol extract (FM3), their TLC profile is shown in Figure 1 and their percent inhibition in various concentrations shown in Table 3. FEA8 became the most have α-glucosidase inhibitory activity, 9,10 but further studies to obtain the active fraction that has α-glucosidase inhibition activity has not been done. The aim of the study is to separate active fraction in the crude extract of G. hombroniana leaves to facilitate obtaining a pure biologically active compound as the α-glucosidase inhibitor.…”
Section: Introductionmentioning
confidence: 99%